Maternal weight as an alternative determinant of the gestational day of Wistar rats housed in individually-ventilated cages. (July 2015) - Paronis, E; Samara, A; Polyzos, A; Spyropoulos, C; Kostomitsopoulos, N G
One of the commonly used animal models in fertility, developmental and neurobiological studies is the laboratory rat. The early recognition of rat pregnancy and confirmation of the exact embryonic day are vital. The aim of this study was to investigate the correlation of maternal weight at the time of conception to its increase throughout gestation, aiming to develop a mathematical model, which can be used for the determination of the exact day of pregnancy, set the threshold, and monitor pregnancy from the onset. We studied a total of 173 Wistar rats with a mean body weight of 238.22 ± 34.9 g. After 72 h at the male's cages, we considered as Day 0 (D0) the day in which a copulatory plug or sperm was found during the vaginal smear examination. After that period the female animals were transferred into their cages, and weight monitoring started 14 days (D14) after D0, until parturition. Based on the statistical analysis, there is a correlation between maternal body weight at D0 and maternal body weight from D14 to D19. Moreover, the average weight gain from D14 to D19 is positively correlated to initial female body weight, while there is no correlation between each pregnant animal's weight from D14 to D19 and litter size. A mathematical model was developed as a tool for the verification of the day of pregnancy. In conclusion, continuous monitoring of maternal weight after D14 can be a reliable method for the recognition of pregnancy and determination of the exact gestational day.